Pemanfaatan Chatgpt Sebagai Media Pendukung Analisis Karya Sastra Arab Bagi Mahasiswa - Dyah Adila Perdana (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The development of Artificial Intelligence (AI) technology has introduced various innovations that support learning processes in higher education. One of the most widely used technologies in education is ChatGPT, a Large Language Model (LLM)-based application capable of generating interactive and contextual text responses. This study aims to examine the utilization of ChatGPT as a supporting medium for Arabic literary works analysis among university students. The research employed a library research method with a qualitative descriptive approach. Data were collected from scholarly sources, including journal articles, books, conference proceedings, and previous studies related to the use of ChatGPT in education and Arabic literary learning. Data analysis was conducted through data collection, reduction, presentation, and conclusion drawing. The findings reveal that ChatGPT possesses several characteristics that support Arabic literature learning, including rapid response generation, high interactivity, accessibility, personalized learning, and multilingual capabilities. In practice, ChatGPT can assist students in analyzing themes, characters and characterization, plot, setting, language style, symbolism, and moral messages in Arabic literary works. Furthermore, its utilization has the potential to enhance students’ critical thinking skills, literary interpretation abilities, digital literacy, academic creativity, and independent learning. Nevertheless, the use of ChatGPT also presents several challenges, such as the risk of inaccurate information (hallucination), technological dependency, and academic integrity issues related to the originality of scholarly work. Therefore, the integration of ChatGPT into Arabic literature learning should be implemented critically, ethically, and systematically while maintaining the role of lecturers as facilitators and students as active learners. This study concludes that ChatGPT has significant potential as a supporting medium for Arabic literary analysis learning in higher education when utilized wisely and responsibly.